2015
DOI: 10.1111/his.12666
|View full text |Cite
|
Sign up to set email alerts
|

Periosteal chondrosarcoma: a histopathological and molecular analysis of a rare chondrosarcoma subtype

Abstract: We report the first large histological and molecular study on periosteal chondrosarcoma showing that histopathological examination and molecular aberrations do not predict prognosis. Although the mutation frequency of IDH1 was low, we confirm the supposed relationship with central chondrosarcoma. Moreover, we identify loss of canonical Wnt signalling and deregulation of pRb signalling as possible events contributing to its histogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 48 publications
(73 reference statements)
0
28
1
Order By: Relevance
“…Loss of p16 protein expression was found to correlate with histological grade of central chondrosarcomas [64]. In dedifferentiated chondrosarcoma, mesenchymal, clear cell chondrosarcoma and periosteal chondrosarcoma, p16 aberrations were found to be common (85,70,95 and 50% of cases, respectively) [14,17]. One study [62 & ] reported that the pRb pathway is affected in 96% of the high-grade central chondrosarcomas, either by a decrease in the amount of CDKN2A/p16 (48%), an increase in the amount of CDK4 (55%) or expression of cyclin D1 (62%).…”
Section: Tumour Suppressor Pathways: Retinoblastoma and P53mentioning
confidence: 92%
See 2 more Smart Citations
“…Loss of p16 protein expression was found to correlate with histological grade of central chondrosarcomas [64]. In dedifferentiated chondrosarcoma, mesenchymal, clear cell chondrosarcoma and periosteal chondrosarcoma, p16 aberrations were found to be common (85,70,95 and 50% of cases, respectively) [14,17]. One study [62 & ] reported that the pRb pathway is affected in 96% of the high-grade central chondrosarcomas, either by a decrease in the amount of CDKN2A/p16 (48%), an increase in the amount of CDK4 (55%) or expression of cyclin D1 (62%).…”
Section: Tumour Suppressor Pathways: Retinoblastoma and P53mentioning
confidence: 92%
“…Inactivation of p53 may result in high levels of two essential negative regulators of p53: MDM2 and MDMX. Overexpression of p53 detected by immunohistochemistry was found in 59% of dedifferentiated chondrosarcomas, 39% of mesenchymal chondrosarcomas, 9% of clear cell chondrosarcomas and not in periosteal chondrosarcomas [14,17]. A significant correlation was observed between overexpression or alteration of the TP53 gene and both the histological grade of the tumour and the presence of metastasis [61].…”
Section: Tumour Suppressor Pathways: Retinoblastoma and P53mentioning
confidence: 94%
See 1 more Smart Citation
“…A specific antibody against the IDH R132H mutation, widely used for the diagnosis of gliomas, permits detection of this mutation by immunohistochemistry in rare chondrosarcoma cases (Figure 4A). IDH mutations are present in 87% of Ollier- associated enchondromas, 86% of secondary central chondrosarcoma, 38–70% of primary central chondrosarcoma, ~15% of periosteal chondrosarcoma and 54% of dedifferentiated chondrosarcoma 5658,75 and are absent in peripheral chondrosarcoma, osteosarcoma and in chordoma. 56,58,76,77 …”
Section: Sarcomas With Simple Genomementioning
confidence: 99%
“…They are typically low or intermediate grade malignancies that originate from the periosteum, firmly distinguishing them from primary CCS [7]. JCS are usually found on the metaphysis or diaphysis of the femur and humerus [8][9][10], and occurrence in the head and neck region is exceedingly rare. These tumors appear to have a positive prognosis with low rates of recurrence, metastases, and a 5-year survival >90% for those with adequate surgical margins [8,10].…”
Section: Introductionmentioning
confidence: 99%